Autolysosomal activation combined with lysosomal destabilization efficiently targets myeloid leukemia cells for cell death - Shah, Harshit; Stankov, Metodi; Panayotova-Dimitrova, Diana; Yazdi, Amir; Budida, Ramachandramouli; Klusmann, Jan-Henning; Behrens, Georg M. N. (Frontiers in Oncology, 2023)
Current cancer research has led to a renewed interest in exploring lysosomal membrane permeabilization and lysosomal cell death as an targeted therapeutic approach for cancer treatment. Evidence suggests that differences in lysosomal biogenesis between cancer and normal cells might open a therapeutic window. Lysosomal membrane stability may be affected by the so-called ‘busy lysosomal behaviour’ characterized by higher lysosomal abundance and activity and more intensive fusion or interaction with other vacuole compartments. Using a panel of multiple myeloid leukemia (ML) cell lines as well as leukemic patient samples, we demonstrated several-fold higher constitutive autolysosomal activity in ML cells as compared to human CD34+ hematopoietic cells. Importantly, we identified mefloquine as a selective activator of ML cells lysosomal biogenesis, which induced a sizable increase in ML lysosomal mass, acidity as well as cathepsin B and L activity. Concomitant mTOR inhibition synergistically increased lysosomal activity and autolysosomal fusion and simultaneously decreased the levels of key lysosomal stabilizing proteins, such as LAMP-1 and 2. As a consequence, mefloquine treatment combined with mTOR inhibition synergistically induced targeted ML cell death without additional toxicity. Taken together, these data provide a molecular mechanism and thus a rationale for a therapeutic approach for specific targeting of ML lysosomes.